Increasing The Tolerance of Grain Corn Plants (Zea mays L.) to High Temperatures by applying Rhizobacteria - Fiqih Arizah Purba; Wan Arfiani Barus; Mohd Aziz Rashid; Syuhaidah Abu Bakar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Corn (Zea mays L.) is a grain crop cultivated in Malaysia, where the kernels are primarily used as feed for animals. Malaysia's climate is generally hot and rainy throughout the year, which has a significant impact on the growth of corn plants (Zea mays L.). This study aims to compare the effects of rhizobacteria on the growth rate and physiological responses of corn seedlings. Rhizobacteria are bacteria that have a positive impact on plant growth. Two strains of heat-tolerant rhizobacteria were used to observe their impact on corn growth: Heat-Tolerant Rhizobacteria 1 (HTR1) and Heat-Tolerant Rhizobacteria 2 (HTR2). Corn seedlings were transplanted into polybags and placed in a controlled environment at 38°C for 14 days, with four bacterial treatment levels: T1 (without HTR), T2 (HTR1), T3 (HTR2), and T4 (a combination of HTR1 and HTR2). Physiological analyses and growth rate measurements showed no significant differences among treatments; however, photosynthesis rates were significantly higher in treatments with rhizobacteria (T2, T3, and T4) compared to the control (T1). These findings suggest that rhizobacteria can enhance plant physiological functions and have potential applications for long-term crop improvement.